2016
DOI: 10.1007/s00192-016-3022-8
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-based stress reduction as a novel treatment for interstitial cystitis/bladder pain syndrome: a randomized controlled trial

Abstract: Purpose Mindfulness-based stress reduction (MBSR) is a standardized meditation program that may be an effective therapy for Interstitial Cystitis/Bladder Pain Syndrome (IC/BPS), a condition exacerbated by stress. The aims of this study were to explore 1) whether MBSR improved IC/BPS symptoms 2) MBSR’s feasibility/acceptability among women with IC/BPS. Materials and Methods This randomized controlled trial included women with IC/BPS undergoing 1st-or 2nd line therapies. Women were randomized to continuation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 22 publications
2
48
0
Order By: Relevance
“…They also help to explain why a multimodal approach addressing the psychosocial aspects of chronic pain may be important in treating IC/BPS. In recent work by our group [31], we found that Mindfulness-Based Stress Reduction improved IC/BPS self-efficacy. The impact of this intervention may be explained by its effect on the isolation aspect of the condition, or perhaps from helping to calm patients’ minds to guard against the unpredictable nature of the process.…”
Section: Discussionmentioning
confidence: 86%
“…They also help to explain why a multimodal approach addressing the psychosocial aspects of chronic pain may be important in treating IC/BPS. In recent work by our group [31], we found that Mindfulness-Based Stress Reduction improved IC/BPS self-efficacy. The impact of this intervention may be explained by its effect on the isolation aspect of the condition, or perhaps from helping to calm patients’ minds to guard against the unpredictable nature of the process.…”
Section: Discussionmentioning
confidence: 86%
“…Although these investigations were all pilot studies and had limited follow‐up, the findings are promising. Those treated reported significant reductions in pain and urinary urgency, had greater perceived control of symptoms, and better healthcare outcomes than controls . The impact of these interventions on psychological states and co‐morbidity has yet to be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, these treatments have been shown to improve pain outcomes such as pain intensity, functional limitations, and psychological distress 57,65 , and they have also been found to reduce ruminative thinking associated with depression, cancer, and school-related stress 14,34,44 . Unfortunately, although mindfulness-related treatment effects have been demonstrated in women 8,38,63,68 , only a few studies have examined their effectiveness in Black individuals and none were focused on pain 16,66,82 . The current results suggest that ongoing clinical and research efforts to better understand pain-related rumination and its responsiveness to different treatments might, among other things, mitigate longstanding race and sex disparities in pain.…”
Section: Discussionmentioning
confidence: 99%